Bioequivalence Study of Vortioxetine Hydrobromide Tablets in Healthy Chinese Subjects Under Fasting and Fed Conditions - Bai W; Song H; Hu Y; Zhang X; Wang X; Guo C; Qiu B; Dong Z (Dove Medical Press, 2023)
Wanjun Bai,1 Haojing Song,1 Yiting Hu,1 Xueyuan Zhang,2 Xiaoru Wang,3 Caihui Guo,1 Bo Qiu,1 Zhanjun Dong1 1Department of Pharmacy, Hebei General Hospital, Shijiazhuang, Hebei, People's Republic of China; 2Shanghai Innovstone Therapeutics Limited, Shanghai, People's Republic of China; 3CSPC Zhongqi Pharmaceutical Technology (Shijiazhuang) Co., Ltd, Shijiazhuang, People's Republic of ChinaCorrespondence: Zhanjun Dong, Department of Pharmacy, Hebei General Hospital, No. 348 Heping West Road, Xinhua District, Shijiazhuang City, Hebei Province, 050051, People's Republic of China, Tel +86 311 85988604, Email 13313213656@126.comObjective: This study compared the pharmacokinetic and safety profiles of generic and original vortioxetine hydrobromide tablets under fasting and fed conditions, and evaluated the bioequivalence of two vortioxetine formulations to obtain sufficient evidence for abbreviated new drug application.Methods: A randomized, open-label, two-formulation, single-dose, two-period crossover bioequivalence study was conducted under fasting and fed conditions (n = 32 per study). Eligible healthy Chinese subjects received a single 10-mg dose of the test or reference vortioxetine hydrobromide tablet, followed by a 28-day washout interval between periods. Serial blood samples were collected up to 72 h after administration in each period, and the plasma concentrations of vortioxetine were detected using a validated method. The primary pharmacokinetic (PK) parameters were calculated using the non-compartmental method. The geometric mean ratios for the PK parameters of the test drug to the reference drug and the corresponding 90% confidence intervals were acquired for bioequivalence analysis. A safety evaluation was performed throughout the study.Results: Under fasting and fed conditions, the PK parameters of the test drug were similar to those of the reference drug. The 90% confidence intervals (CIs) of the geometric mean ratios of the test to reference formulations were 96.44- 105.81% for peak concentration (Cmax), 97.94- 105.05% for the area under the curve truncated at 72 hours (AUC0-72 h) under fasting conditions, 93.92- 104.15% for Cmax, and 96.67- 102.55% for AUC0-72 h under fed conditions, all of which were within the accepted bioequivalence range of 80.00- 125.00%. Both the test and reference formulations were well-tolerated, and no serious adverse events related to the study drug were reported during the study.Conclusion: The PK bioequivalence of the test and reference vortioxetine hydrobromide tablets in healthy Chinese subjects was established under fasting and fed conditions, which met the predetermined regulatory criteria. Both formulations were safe and well tolerated.Keywords: vortioxetine, bioequivalence, pharmacokinetics, safety